Development in Peril: Assessing Education Opportunities in Post-Conflict South Waziristan - Saad Ullah Shaheen; Jannat Noor Lodhi; Omar Masoom Wazir; Muhammad Tanveer Jamal; Hamayun Khan (`, 2025)
This study explores the complex dynamics surrounding educational opportunities in post-conflict South Waziristan, a region that has long grappled with instability, militarization, and socio-cultural constraints. The study examines key barriers affecting access to education in the area. Furthermore, the study also assesses the role of government, local community, NGOs, and international aid agencies in shaping educational outcomes in the area. The present study uses a mixed methodology research approach, and data was gathered using interview guides and questionnaires from respondents, including community people, government officials, and NGO workers. The study findings reveal that while some progress has been made in the education sector, particularly regarding schools’ infrastructure development, challenges still persist that restrict educational opportunities in the area. The study found various challenges, such as security checkpoints, curfews, economic hardship, gender-based differences, and inadequate communication infrastructure, are some of the major challenges people face. Cultural norms and limited mobility in post-conflict situations continue to disproportionately affect girls. Half of the respondents reported feeling unsafe attending schools, and a majority rated the education system as either ineffective or average after the conflict. The study findings show that despite the presence of various national education and development policies, gaps in implementation, lack of coordination between civil and military, and weak community ownership continue to undermine efforts toward inclusive and sustainable educational outcomes. Keywords: Post-Conflict, Education, South Waziristan, Development Challenges